Unlocking myeloma's spatial world at the micrometer scale - Rasche, Leo; Weinhold, Niels (Blood, 2025)
In this issue of Blood, Yip et al(1) apply spatial transcriptomics to bone marrow (BM) trephine biopsies to investigate the interplay between tumor-cell sub-populations and the tumor microenvironment (TME) in precursor stages and newly-diagnosed multiple myeloma (MM). Their study yields 2 major findings. First, spatial transcriptomics is feasible on BM trephines when optimized sample processing methods are used. Second, and most intriguingly, they provide evidence that distinct plasma-cell subpopulations can locally shape the TME. For example, plasma-cell subpopulations with an inflammatory phenotype were enriched in regions with a high T-cell density. Notably, the differences in cellular composition between distinct intratumoral neighborhoods were more pronounced than those observed between precursor stages and MM, with no consistent TME changes across disease stages. As outlined by the authors, these findings challenge the prevailing assumption that universal BM-wide changes in the TME are the primary drivers of disease progression in plasma-cell dyscrasias. Instead, they underscore the need to account for tumor-intrinsic factors when interpreting alterations within the TME.